The accuracy of edentulous arch impression between intraoral scanner and laboratory scanner: a scoping review - Athiyyah Aura Achmadi; Rasmi Rikmasari; Fahmi Oscandar; Vita Mulya Passa Novianti (BDJ Open)
Abstract Objective This study aims to compare the utilization of intraoral scanners and laboratory scanners as an alternative impression method in fully and partially edentulous cases. Materials and methods This scoping review that implemented the PRISMA-ScR instrument and the methodological approach by Arksey and O’Malley. A comprehensive search was conducted across four databases (PubMed, Scopus, SpringerLink, and ScienceDirect) to retrieve articles published within the last decade. Inclusion criteria were established to identify articles that analyzed the accuracy of both intraoral scanners and laboratory scanners in edentulous cases. Data extraction was performed and results were presented in tables. Subsequently, a thematic analysis was conducted to conclude the accuracy of the intraoral scanners and laboratory scanners in edentulous cases. Results A total of 312 articles were retrieved from four databases. After eliminating duplicates and screening based on titles, abstracts, and eligibility criteria, eight articles were selected for detailed analysis of the accuracy of each technology. Most studies investigated fully and partially edentulous arches and demonstrated the utilization of intraoral scanners and laboratory scanners. Some studies additionally analyzed the correlation between various factors influencing digital scans and the condition of edentulous arch. Evaluations of edentulous digital impressions have been conducted, with an assessment of the reliability of intraoral scanners and laboratory scanners. Conclusion Intraoral scanners are extensively utilized and demonstrate considerable promise for edentulous impression procedures. However, morphological differences may impact scanning outcomes.